Hyperbaric oxygen therapy for long COVID (HOT-LoCO), an interim safety report from a randomised controlled trial - Anders Kjellberg; Adrian Hassler; Emil Boström; Sara El Gharbi; Sarah Al-Ezerjawi; Jan Kowalski; Kenny A. Rodriguez-Wallberg; Judith Bruchfeld; Marcus Ståhlberg; Malin Nygren-Bonnier; Michael Runold; Peter Lindholm (BMC Infectious Diseases, 2023)
Abstract Background With ~ 50 million individuals suffering from post-COVID condition (PCC), low health related quality of life (HRQoL) is a vast problem. Common symptoms of PCC, that persists 3 months from the onset of COVID-19 are fatigue, shortness of breath and cognitive dysfunction. No effective treatment options have been widely adopted in clinical practice. Hyperbaric oxygen (HBO2) is a candidate drug. Methods The objective of this interim analysis is to describe our cohort and evaluate the safety of HBO2 for post covid condition. In an ongoing randomised, placebo-controlled, double blind, clinical trial, 20 previously healthy subjects with PCC were assigned to HBO2 or placebo. Primary endpoints are physical domains in RAND-36; Physical functioning (PF) and Role Physical (RP) at 13 weeks. Secondary endpoints include objective physical tests. Safety endpoints are occurrence, frequency, and seriousness of Adverse Events (AEs). An independent data safety monitoring board (DSMB) reviewed unblinded data. The trial complies with Good Clinical Practice. Safety endpoints are evaluated descriptively. Comparisons against norm data was done using t-test. Results Twenty subjects were randomised, they had very low HRQoL compared to norm data. Mean (SD) PF 31.75 (19.55) (95% Confidence interval; 22.60–40.90) vs 83.5 (23.9) p < 0.001 in Rand-36 PF and mean 0.00 (0.00) in RP. Very low physical performance compared to norm data. 6MWT 442 (180) (95% CI 358–525) vs 662 (18) meters p < 0.001. 31 AEs occurred in 60% of subjects. In 20 AEs, there were at least a possible relationship with the study drug, most commonly cough and chest pain/discomfort. Conclusions An (unexpectedly) high frequency of AEs was observed but the DSMB assessed HBO2 to have a favourable safety profile. Our data may help other researchers in designing trials. Trial Registration ClinicalTrials.gov: NCT04842448. Registered 13 April 2021, https://clinicaltrials.gov/ct2/show/NCT04842448 . EudraCT: 2021-000764-30. Registered 21 May 2021, https://www.clinicaltrialsregister.eu/ctr-search/trial/2021-000764-30/SE